2021
DOI: 10.3390/atmos12111413
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Dust Exposure and Hospitalizations in El Paso, Texas, USA

Abstract: The Southwestern USA has been identified as one of the most persistent dust-producing regions of North America, where exposure to inhalable particulate matter (PM10) originating from desertic landscape during dust events/dust exposures (DEs) can reach hazardous levels. El Paso, Texas’s ambient air has reached hazardous levels of PM10 from dust with near zero visibility due to these natural events originating in the surrounding Chihuahuan Desert. The aim of this study was to investigate whether dust exposures i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Different studies that examined the impact of dust on human health in the USA, either focused on one region (Comrie, 2021 ; Grineski et al., 2011 ; Hefflin et al., 1994 ; Herrera‐Molina et al., 2021 ; Ostro et al., 1999 ) or the entire USA (Crooks et al., 2016 ; Jones, 2020 ; Rublee et al., 2020 ). In some studies, environmental observations such as wind speed, PM concentrations from nearby air quality monitors, and/or reported weather codes from nearby ASOS were used to identify dust events (Grineski et al., 2011 ; Herrera‐Molina et al., 2021 ), while others used the Storm Events Database (SED) as the source of their DS dataset (Crooks et al., 2016 ; Jones, 2020 ; Rublee et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies that examined the impact of dust on human health in the USA, either focused on one region (Comrie, 2021 ; Grineski et al., 2011 ; Hefflin et al., 1994 ; Herrera‐Molina et al., 2021 ; Ostro et al., 1999 ) or the entire USA (Crooks et al., 2016 ; Jones, 2020 ; Rublee et al., 2020 ). In some studies, environmental observations such as wind speed, PM concentrations from nearby air quality monitors, and/or reported weather codes from nearby ASOS were used to identify dust events (Grineski et al., 2011 ; Herrera‐Molina et al., 2021 ), while others used the Storm Events Database (SED) as the source of their DS dataset (Crooks et al., 2016 ; Jones, 2020 ; Rublee et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Eye irritation is one of the most common health outcomes associated with hospital admission at the time of dust storms in Asia and the Middle East [5,39]. In a recent study in the southwestern US in which sound meteorological and PM data were available, small but statistically significant effects were found between sand and dust storms and hospitalizations for a range of health outcomes on the day and within a seven-day period after dust exposure [40]. Other studies have shown short-term effects of dust storms on the risk of mortality in Kuwait [41], Taipei [42], and Iran [43].…”
Section: Discussionmentioning
confidence: 99%
“…Increased odds of hospitalization for asthma and acute bronchitis were detected on dust days and for up to 3 days thereafter in El Paso, Texas, with the greatest impacts being seen in children (especially girls, for acute bronchitis) and persons with low income (Grineski et al, 2011). Herrera-Molina et al (2021) found the relative risks of hospitalizations for multiple diseases over a 5-year period in El Paso were significantly associated with windblown dust exposure on the day of the event and for up to 7 days later. Rodopoulou et al (2014) noted a connection between concentrations of PM 10 and PM 2.5 and emergency room utilization for cardiovascular conditions in the warm season in Las Cruces, New Mexico, USA, where blowing dust is frequent.…”
Section: Other Morbidity Effectsmentioning
confidence: 98%
“…Herrera‐Molina et al. (2021) found the relative risks of hospitalizations for multiple diseases over a 5‐year period in El Paso were significantly associated with windblown dust exposure on the day of the event and for up to 7 days later. Rodopoulou et al.…”
Section: Effects On Human Healthmentioning
confidence: 99%